Elisabeth Kontogiorgi, Population Exchange in Greek Macedonia: The Rural Settlement of Refugees 1922-1930, New York: Oxford University Press, 2006, 396 pages. - Alpan, Aytek Soner (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 2015)
[ Δε διατίθεται περίληψη / no abstract available]